2016
DOI: 10.1002/jnr.23910
|View full text |Cite
|
Sign up to set email alerts
|

Lithium improves cell viability in psychosine‐treated MO3.13 human oligodendrocyte cell line via autophagy activation

Abstract: Globoid cell leukodystrophy (GLD) is a rare, rapidly progressing childhood leukodystrophy triggered by deficit of the lysosomal enzyme galactosylceramidase (GALC) and characterized by the accumulation of galactosylsphingosine (psychosine; PSY) in the nervous system. PSY is a cytotoxic sphingolipid, which leads to widespread degeneration of oligodendrocytes and Schwann cells, causing demyelination. Here we report on autophagy in the human oligodendrocyte cell line MO3.13 treated with PSY and exploitation of Li … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 64 publications
4
37
0
Order By: Relevance
“…Autophagosomes bind to lysosomes and create an autolysosome and its contents are degraded by lysosomal hydrolysis. In accordance with our study, also previous studies showed the protective effects of lithium in autophagy induction (29) in oligodendrocytes (30), microglia (31), endothelial cells (32), dopaminergic neurons (33), cerebel- lar cells (34), and PC12 cells (9). In addition, lithium also plays a protective role in autophagy induction in many diseases such as: spinal cord injury (35), amyotrophic lateral sclerosis, prion, Parkinson's disease and colorectal cancer (36).…”
Section: Discussionsupporting
confidence: 92%
“…Autophagosomes bind to lysosomes and create an autolysosome and its contents are degraded by lysosomal hydrolysis. In accordance with our study, also previous studies showed the protective effects of lithium in autophagy induction (29) in oligodendrocytes (30), microglia (31), endothelial cells (32), dopaminergic neurons (33), cerebel- lar cells (34), and PC12 cells (9). In addition, lithium also plays a protective role in autophagy induction in many diseases such as: spinal cord injury (35), amyotrophic lateral sclerosis, prion, Parkinson's disease and colorectal cancer (36).…”
Section: Discussionsupporting
confidence: 92%
“…Among the most well-established functions of lithium ion is the phosphorylation and inhibition of GSK3β and as well as upregulating levels of BDNF and stimulating anti-apoptotic signaling ( Rowe and Chuang, 2004 ; Wada et al, 2005 ; Young, 2009 ; Pasquali et al, 2010 ). Additionally, lithium ion can promote autophagy, which can be neuroprotective, although this was observed at millimolar doses in vitro ( Motoi et al, 2014 ; Del Grosso et al, 2016 ; Liu et al, 2017 ), and at 50 mg/kg in vivo ( Liu et al, 2017 ), doses much higher than those used here. Lithium ion has also been shown to delay disease progression of amyotrophic lateral sclerosis (ALS) in humans and in the mouse G93A model of the disease ( Fornai et al, 2008 ).…”
Section: Discussionmentioning
confidence: 59%
“…Recently, we performed a drug screen to identify compounds that block the binding of proNGF to cells expressing sortilin and p75 NTR , and lithium citrate was among these compounds. Lithium ion can inhibit apoptosis by a variety of different mechanisms ( Wada et al, 2005 ), including increasing Akt activity, by phosphorylating and inactivating GSK3β ( Tajes et al, 2009 ; Pasquali et al, 2010 ), and promoting autophagy ( Motoi et al, 2014 ; Del Grosso et al, 2016 ; Liu et al, 2017 ). Chronic treatment with lithium has also been shown to upregulate BDNF expression in the brain ( Fukumoto et al, 2001 ) and retina ( Wu et al, 2014 ), which provides another potential neuroprotective mechanism for lithium ion.…”
Section: Introductionmentioning
confidence: 99%
“…In general, in vivo biological evaluation will be carried out after in vitro biological evaluation is qualified, and finally clinical research could be carried out. MSCs viability test can evaluate the cytocompatibility of materials by evaluating the viability of MSCs on bioactive materials [ [42] , [43] , [44] , [45] ]. MSCs proliferation could be regulated by bioactive materials.…”
Section: The Latest Research Progress Of Traditional Characterizationmentioning
confidence: 99%